Readers Researching Their Reading: Creating a Community of Inquiry - Parsons, Linda T. (Language arts, 2009)
This article explores how a group of ten fourth-grade students who were avid readers became a community of inquiry. Because the children’s reading experiences mattered to them, they were intrigued by documenting how they created, entered, and sustained the world of the story, and this fostered a spirit of inquiry.